Hubungan modal sosial dan pendapatan projek ekonomi peserta Amanah Ikhtiar Malaysia (AIM) Wilayah Kedah dan Kelantan - Noor, Mohd Saifoul Zamzuri; Hussin, Fauzi; Ishak, Mohd Sobhi (2013)
Social capital has long been discussed by social scientists as well as in the economic sphere i.e. Narayan and Cassidy (2001), Putnam et al.(1993) and Coleman (1988). Lately, however, its discussion has become more interesting because of its importance in economic development, especially relating to micro financing and its relationship to poverty. The microfinance scheme approach which nourishes the existing social capital amongst the schemes participants is said to be capable of raising the performance of their economic activities.This study also attempts to use the structural equation model (SEM) which is rarely used in economic analysis in examining the effects of four variables, namely social capital, human capital, financial capital and physical capital on the participants‟ income from economic projects. The data set for this study was obtained from' Kajian Penyelidikan Impak 6 Amanah Ikhtiar Malaysia‟ (AIM).A total of 489 respondents were interviewed using the face-to-face interview method.The respondents were selected using the stratified random sampling based on branches in both Kedah and Kelantan. The findings show that social capital, as well as the factors of human capital, financial capital, and physical capital, has a significant effect in increasing the income of AIM project participants. Analyses by regions and by length of time as an AIM member also show significant effect on the project income of members.The findings illustrate that investment for the improvements of social capital is also crucial to achieve socio-economic development objectives.